Phytochemical Screening and Antibacterial Test of Ethanolic Extract of Kawista (Limonia acidissima L.) from Aceh Besar against Escherichia coli - Audia Anda Rini; Supriatno Supriatno; Hafnati Rahmatan (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Kawista is one of plant that is used as traditional medicine. One of the utilization of kawista is the consumtion of this unripe fruit to cure diarrhea. Etanolic extract of this fruit contains phytochemical components that has antibacterial activity. Study about Phytochemical Screening and Antibacterial Test of Ethanolic Extract of Kawista from Aceh Besar against Escherichia coli has been conducted on June 27 until July 14, 2016. The aims of the study is to determine phytochemical contents of ethanolic extract of fruit pulp of kawista and the effect of various concentrations against the growth of E. coli. Kawista which is used in the study gained from Aceh Besar. Phytochemical test showed that ethanolic extract of fruit pulp of kawista contain various active compounds such as alkaloids, saponins, tannins, triterpenoids, and polyphenols. E. coli that is used in this study were obtained from Microbiology Laboratory of Veterinary Faculty, Syiah Kuala University. The method used in the study is laboratory experiment using a quantitative type of Completely Randomized Design (CRD), which are divided into 7 groups, 5 treatment groups (ethanolic extract of fruit pulp of kawista) and 2 control groups using aquades (negative control) and streptomycin (positive control). Data analysis was performed by using ANOVA (Analysis of Variance) and then proceed with the test of HSD (Honestly Significant Difference) at α 5%. Antibacterial test results showed ethanolic extract of fruit pulp of kawista could inhibit the growth of E. coli (317.5 2.85). The highest inhibitory zone obtained at 500.000 ppm, with an average diameter of 16.141 mm. Conclusion of the study is showing that the extract of kawista pulps has antibacterial activity against E. coli bacterial growth. The higher concentration of the extract, the greater antibacterial activity against E. coli bacterial growth. Keywords: Ethanolic extract of kawista, antibacterial, Escherichia coli.